Effectiveness of Health Education Using Audiovisual Media on Psychomotor Ability to Wash Hands in Children with Special Needs - Novia Nazirun; Merlina Sari (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the effectiveness of health education using audiovisual media on the psychomotor ability of hand washing in children (with mental retardation). Children with special needs need special care and get a subject called self-development. Children are taught healthy living behaviours. This study used an experimental method with a one-group pre-test and post-test approach consisting of one intervention group. The sampling technique uses a total sampling technique: as many as 25 children were selected in the intervention class. Data analysis using the Wilcoxon Signed Rank test. The results of this study: 1) The level of psychomotor ability to wash hands before being given audiovisual media to children with special needs (Tunagrahita) at SLB Pelita Nusa in Pekanbaru 68% Incapable, 2) The level of psychomotor ability to wash hands after being given audiovisual media to children with special needs (Tunagrahita) at SLB Pelita Nusa in Pekanbaru increased to Independent with 80% of respondents, 3) Audiovisual media learning is effective for improving psychomotor handwashing skills in children with special needs (Tunagrahita) at SLB Pelita Nusa in Pekanbaru, Riau. Based on the study's results, it can be concluded that audiovisual media effectively improves the psychomotor ability of hand washing in children with special needs (Tunagrahita) at SLB Pelita Nusa in Pekanbaru, Riau.